Greek Translation, Cultural Adaptation and Validation of the Mini Sarcopenia Risk Assessment Questionnaire, to Evaluate Sarcopenia in Greek Elderly at a Hospital Setting - Anna Pantouvaki; Grigorios Kastanis; Evridiki Patelarou; Kalliopi Alpantaki; Christos Kleisiaris; Michail Zografakis-Sfakianakis (MDPI AG, 2023)
Sarcopenia is a progressive aging syndrome with severe socioeconomic costs. Therefore, the early diagnosis of sarcopenia is required to secure early treatment and to enhance quality of life. The Mini Sarcopenia Risk Assessment (MSRA) questionnaire, which is available in seven-item (MSRA-7) and five-item (MSRA-5) versions, is a sarcopenia screening tool that was translated into Greek, adapted, and validated in this study. The present study was developed in an outpatient hospital setting, from April 2021 to June 2022. The MSRA-7 and MSRA-5 questionnaires were translated backwards and forwards and adapted to the Greek language. To validate the MSRA questionnaire as a pre-screening tool to identify the risk of sarcopenia in the older Greek population, both the MSRA-7 and MSRA-5 versions were correlated with the Greek version of the SARC-F questionnaire, which is a widely accepted and well-known tool used in sarcopenia screening. Ninety elderly subjects aged 65-89 years-old with no mobility impairments participated in this study. The questionnaires' content validity was assessed using the Content Validity Ratio, and the Content Validity Index was calculated for the instrument. The intra-rater reliability was assessed by calculating the Intra-class Correlation Coefficient between the initial assessment and the reassessment of the MSRA questionnaire, which was 0.986, with a 95% Confidence Interval of 0.961-0.995. Concurrent validity was assessed between the Greek MSRA questionnaires and the SARC-F questionnaire using the Spearman's rank correlation coefficient (p). The Greek MSRA-7 questionnaire had a very high correlation with the SARC-F questionnaire (rho = −0.741, p < 0.001), as did the Greek MSRA-5 questionnaire (rho = −0.724, p < 0.001). The proofs of content validity, concurrent validity, and intra-rater reliability provided for the Greek versions of the MSRA, designated them as reliable pre-screening tools for the detection of sarcopenia in the older population and in clinical practice.